Stiffness-based method to identify the threshold load of low hardness steels using the Incremental step loading test. (December 2022) - Antonelli Martiniano, Guilherme; Eduardo Silveira Leal, José; Torres Piza Paes, Marcelo; Wladimir Bose Filho, Waldek; Domingues Franco, Sinésio
Highlights: A new method to identify the Pth obtained on the ISL test was proposed. A stiffness-based method was developed to identify the Pth of low hardness steels tested using ISL. A revision of the ASTM F1624 standard was performed. Analysis of the influence of step time and strain rate on the ISL results. Evaluation of the hardness effect on the hydrogen embrittlement susceptibility. Abstract: Hydrogen embrittlement (HE) is one of the main problems related to the use of metallic materials in sour or wet environments. The Incremental Step-Loading (ISL) test used to evaluate the susceptibility to HE of steels has gained more visibility over recent years, thus allowing for the determination of the threshold load (Pth ) in H+ enriched environments. However, the ISL standard, ASTM F1624, limits the test to steels with a minimum hardness of 33 HRC. Even for those steels with 33 HRC, the results present some misinterpretations. In addition to this fact, one needs to consider that there are several applications where steels with hardness below 33 HRC are used, as for instance, in fasteners and tool joints under cathodic protection used in the oil and gas industry, for which hardness varies from 26 to 32 HRC. In light of the aforementioned, the standard limitation represents a major disadvantage related to the application of the ISL test. Grounded upon the said, the aim of the present study is to propose a methodology based on the specimen stiffness to be used in the ISL test results, allowing the Pth determination of steels with hardness lower than 33 HRC. Conventional and extended ISL tests were performed in two steels (4137-M and 4130-M) with a 32 HRC hardness values. Applying the stiffness-based method on the the conventional ISL test results, a threshold load (Pth ) of 71.5 %PFFS and 66.0 %PFFS were found for the 4137-M and 4130-M steels, respectively. To validate these results, extended ISL tests were performed on both steels and the results showed a Pth of 73.7 %PFFS for the 4137-M steel and 66.0 %PFFS for the 4130-M steel. The results from the conventional ISL test, using the stiffness-based method proposed in this study, provided values similar or with differences lower than 5 %PFFS, when compared alongside the extended ISL tests. Moreover, ISL tests were performed on the same steels with 40 HRC hardness, and the AISI4137-M presented a Pth of 21.6 %PFFS and for 4130-M the Pth was 22.0 %PFFS . The main conclusion obtained from these tests was that, when large amount of plastic deformation is not present on ISL test, the load drop visual detection is sufficient to determine the Pth . As expected, it was observed that both steels with 40 HRC presented higher HE susceptibility than the 32 HRC ones. This behavior was due to higher stress concentration at the notch root presented by the higher hardness condition. The stiffness-based method proved to be robust and capable of separate yielding from hydrogen induced cracking of low hardness steels and could also be used to identify the Pth values of steels with hardness lower than that specified by the ASTM F1624 standard, and which are tested using the ISL test.